220 Cochrane review of interval brain imaging in adults with cerebral glioma. Issue 6 (27th May 2022) - Thompson, Gerry; Lawrie, Tess; Kernohan, Ashleigh; Jenkinson, Michael; Grant, Robert
Abstract : Background: It is not known whether imaging at pre-specified time points after glioma diagnosis and treatment leads to better outcomes than triggered imaging performed in response to new or worsening symptoms. Objectives: To systematically review the effect of different imaging strategies on health and economic outcomes for adults with cerebral glioma (grade 2 to 4). Methods: CENTRAL, MEDLINE and Embase were searched up to 18/06/2019 for relevant RCTs and non- randomised studies comparing imaging strategies in adults with glioma. The NHS Economic Evaluation Database (EED) was also searched for relevant economic evaluations. We used standard Cochrane review methodology. Findings: We included one retrospective study comparing early post-operative imaging (within 48 hours) with no early post-operative imaging among 125 adults with glioblastoma. Evidence suggested little or no difference in survival between approaches at one year (RR 0.86, 95% CI 0.61 to 1.21; 48% vs 55% died, respectively) and two years after diagnosis (RR 1.06, 95% CI 0.91 to 1.25; 86% vs 81% died, respectively) but was assessed as very low quality. No economic evaluations were found. Conclusions: The effect of different imaging strategies on survival and other health outcomes remains largely unknown. Existing imaging schedules seem to be pragmatic rather than evidence-based. robin.grant@luht.scot.nhs.uk